2023
DOI: 10.7759/cureus.41384
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Carotid Plaque Size, Carotid Intima-Media Thickness, Resistive Index, and Pulsatility Index With Acute Ischemic Stroke

Abstract: Background: Carotid atherosclerosis is an important etiological factor for ischemic stroke. Early carotid lesion detection may prevent further strokes. Doppler ultrasound measures carotid artery blood flow, intimamedia thickness, stenosis, plaques, and lumen and wall changes.Objective: The objective of this study is to determine the association of carotid plaque size (CPS), carotid intima-media thickness (CIMT), resistive index (RI), and pulsatility index (PI) with acute ischemic stroke.Methodology: A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Detection of plaques, stenosis, and IMT on carotid Doppler ultrasound can prevent further strokes. In ischemic stroke cases, IMT was found to be 0.79±0.10 mm on the right side and 0.90±0.17 mm on the left, and CIMT was found to be significantly higher in the case group than in the control group [11]. In our study, the mean CIMT thickness was found to be significantly higher in individuals with significant stenosis in the CCA and ICA (0.82±0.13).…”
Section: Discussionsupporting
confidence: 43%
“…Detection of plaques, stenosis, and IMT on carotid Doppler ultrasound can prevent further strokes. In ischemic stroke cases, IMT was found to be 0.79±0.10 mm on the right side and 0.90±0.17 mm on the left, and CIMT was found to be significantly higher in the case group than in the control group [11]. In our study, the mean CIMT thickness was found to be significantly higher in individuals with significant stenosis in the CCA and ICA (0.82±0.13).…”
Section: Discussionsupporting
confidence: 43%